Ergonomic and usability evaluations of physical and digital products developed in research within a professional master’s program in Ergonomics: a survey of the methods and tools used - Acioly, Angélica de Souza Galdino; Vitorino, Danilo Fernandes; Pichler, Rosimeri Franck (DAT Journal, 2025)
This article presents a systematic review of ergonomic and usability evaluation methods applied to physical and digital products in research conducted within the scope of the Graduate Program in Ergonomics (PPErgo) at the Federal University of Pernambuco (UFPE). Using the Snowballing technique, 13 master’s dissertations defended from 2015 to 2025 and 22 related articles were analyzed. The results indicate a predominance of subjective methods, such as surveys and discomfort scales, followed by more objective approach techniques, including electromyography and biomechanical modeling. A limited use of accessibility checklists and performance metrics was observed. Most dissertations resulted in technical recommendations. The analyses revealed good methodological practices, but also gaps in terms of standardization, accessibility, and practical experimentation. This study contributes to understanding the approaches adopted in the context of professional ergonomics education, offering insights to enhance both training and the applicability of research in the field.